Seroprevalence of antibodies against severe acute respiratory coronavirus 2 (SARS-CoV-2) in household dogs in Japan - ITO, Genta; GOTO-KOSHINO, Yuko; KURODA, Yudai; EUNSIL, Park; MAEDA, Ken; SOMA, Takehisa; MOMOI, Yasuyuki (Journal of Veterinary Medical Science, 2021)
We investigated the seroprevalence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) among dogs in the Tokyo area via enzyme-linked immunosorbent assay (ELISA) using the spike protein as the target antigen. Plasma samples from 494 household dogs and blood-donor dogs were tested from July 2020 to January 2021. Of these samples, three showed optical densities that were higher than the mean plus two standard deviations of the mean of the negative-control optical densities (ODs). Of these three samples, only the sample with the highest OD by ELISA was confirmed positive by virus neutralization testing. The positive dog presented no SARS-CoV-2-related symptoms. The positivity rate of SARS-CoV-2 infections among dogs in the Tokyo area was approximately 0.2%.